2015
DOI: 10.1111/cogs.12319
|View full text |Cite
|
Sign up to set email alerts
|

Phonological Concept Learning

Abstract: Linguistic and non-linguistic pattern learning have been studied separately, but we argue for a comparative approach. Analogous inductive problems arise in phonological and visual pattern learning. Evidence from three experiments shows that human learners can solve them in analogous ways, and that human performance in both cases can be captured by the same models. We test GMECCS (Gradual Maximum Entropy with a Conjunctive Constraint Schema), an implementation of the Configural Cue Model (Gluck & Bower, ) in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
59
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 145 publications
(267 reference statements)
8
59
2
Order By: Relevance
“…A range of proposed psychological mechanisms is compatible with this pattern of results, however. We have focused on an interpretation in which participants judged the test words for acceptability by evaluating whether the test words followed one or more probabilistic generalizations extracted during the exposure phase (Albright & Hayes, 2003;Hayes & Wilson, 2008;Frank & Tenenbaum, 2011;Linzen & O'Donnell, 2015;Moreton et al, 2015). Yet the same results may be consistent with a view in which participants evaluate the similarity between the consonant pattern of the test word and their memories of the consonant patterns in the exposure words (Goldinger, 1998;Nosofsky, 1986;Redington & Chater, 1996).…”
Section: Mechanisms Of Generalizationmentioning
confidence: 98%
See 4 more Smart Citations
“…A range of proposed psychological mechanisms is compatible with this pattern of results, however. We have focused on an interpretation in which participants judged the test words for acceptability by evaluating whether the test words followed one or more probabilistic generalizations extracted during the exposure phase (Albright & Hayes, 2003;Hayes & Wilson, 2008;Frank & Tenenbaum, 2011;Linzen & O'Donnell, 2015;Moreton et al, 2015). Yet the same results may be consistent with a view in which participants evaluate the similarity between the consonant pattern of the test word and their memories of the consonant patterns in the exposure words (Goldinger, 1998;Nosofsky, 1986;Redington & Chater, 1996).…”
Section: Mechanisms Of Generalizationmentioning
confidence: 98%
“…In Experiment 2a, for example, only four consonants were ever repeated in a word: , 5 It is unclear if the specific procedure advocated by Hayes and Wilson (2008) would be sufficient to simulate the results; we were unable to the run the code available online on our materials since it requires at least 3000 training items. GMECCS, the other published maximum entropy model (Moreton et al, 2015), does not make clear predictions about the relationship between the amount of exposure data and the generalization being acquired; the authors do report gradual convergence towards the target distribution after multiple steps ('trials') of their learning algorithm, but the relationship between the number of trials and the number of observed data points is unclear (hundreds of such 'trials' appear to correspond to a single training example). See Linzen and O'Donnell (2015) for an implementation of a maximum entropy model that is sensitive to the amount of training data in a more straightforward fashion.…”
Section: Sustained Generalizationmentioning
confidence: 99%
See 3 more Smart Citations